Location analysis of informal businesses along the activity route in the township of Galeshewe, Kimberley - Mathews, Marvin Henwill (University of the Free State, 2016)
Whether the South African public likes it or not, the informal economy is an important part of many urban inhabitants' lives, be it as a source of business and income or as a source of services to the community. The importance of the informal economy in developing nations is not truly appreciated or planned for and in many cases is merely seen as a nuisance, thus ignorant to the potential that exists in the informal economy. The Galeshewe Activity Route is located in the city of Kimberley and was envisaged to link the economic and social nodes of the township Galeshewe through a linear road network that would in turn attract investment and business to the areas along the Route. The development of the Activity Route has led to an unplanned occurrence of informal businesses developing along the Route. Many of these informal businesses tend to be established at specific locations on the Route and seem to have thrived for years. The purpose of this research is therefore to add knowledge to the understanding of informal businesses. This dissertation aims to determine how factors such as the services and products provided by informal businesses, the land use layout of the Galeshewe Activity Route along which the informal business are located, and the informal business regulatory framework influence the decisions informal business owners make in choosing the location of the ir businesses along the Activity Route Understanding the informal economy better will enlighten our knowledge in relation to township economics, where the informal economy thrives and a large portion of South Africa's urban population are inhabitants.
Dissertation (M.U.R.P. (Urban and Regional Planning))--University of the Free State, 2016
Keywords: Street trading; Informal economy; Home-based trading; Informal business clustering; Informal trading policy; Informal trader; Activity Route; Socio-spatial dynamics; Township economics; Street vendors -- South Africa -- Northern Cape -- Kimberley; Informal sector (Economics) -- South Africa -- Northern Cape -- Kimberley